2019
DOI: 10.1111/jfbc.12840
|View full text |Cite
|
Sign up to set email alerts
|

Association of preharvest management with oxidative protection and enzymatic browning in minimally processed cassava

Abstract: The aim of this study was to examine oxidative protection and enzymatic browning in the storage of minimally processed cassava and their relationship with population density and harvest age. Population densities were 1.0, 1.25, 1.5, and 1.75 plants m−2. After being harvested at 300, 360, or 420 days after planting, cassava were minimally processed and stored at 5 ± 2°C. It was observed that superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) play key roles in the tolerance of young roots to browni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
(52 reference statements)
3
11
0
Order By: Relevance
“…These phenolic acids have been identified in the literature as active phytochemicals with varying sources, degrees and specificity of scavenging abilities [31,[34][35][36][37] in diverse plants other than cassava. Literature abounds on the total phenolic content of cassava root, [38,39] however that of the phenolic acid profile is rare. Irondi et al [40] studied the phenolic composition of cassava flour using HPLC and identified five phenolic acids; chlorogenic, caffeic, rutin, gallic and quercetin acids.…”
Section: Metabolic Profile Of M Esculenta Root Parenchymamentioning
confidence: 99%
“…These phenolic acids have been identified in the literature as active phytochemicals with varying sources, degrees and specificity of scavenging abilities [31,[34][35][36][37] in diverse plants other than cassava. Literature abounds on the total phenolic content of cassava root, [38,39] however that of the phenolic acid profile is rare. Irondi et al [40] studied the phenolic composition of cassava flour using HPLC and identified five phenolic acids; chlorogenic, caffeic, rutin, gallic and quercetin acids.…”
Section: Metabolic Profile Of M Esculenta Root Parenchymamentioning
confidence: 99%
“…The surface analyses described in this study corresponded to the 5 mm of the surface, including the periderm (Fig. 1), as described by Coelho et al ., 26 which is the region where oxidative responses to damage are most transient. To intensify the cutting into the tissues, we chose the abrasion technique (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The roots were harvested fourteen months after planting and sorted before washing with tap water generously to remove adhering dirt and avoid contamination during processing. Within 24 h after harvest, processing commenced after ascertaining that the roots were in a fresh state, before the onset of deterioration [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of chemicals regarded as safe, such as calcium chloride, citric acid, and ascorbic acid, in food processing to control enzymatic browning and discoloration is a common practice. There is available literature on the use of ascorbic acid and citric acid in the treatment of white yam flour [ 10 ]; the use of sulphite, calcium chloride, and citric acid in the treatment of potato flour [ 11 , 12 ]; and the use of calcium chloride treatment for the control of enzymatic browning of minimally processed cassava chips [ 13 , 14 ]. However, there is sparse literature on the use of safe chemical pretreatment in the processing of cassava flour.…”
Section: Introductionmentioning
confidence: 99%